Saccharose cluster ions as mass calibrants in positive-ion direct analysis in real time-mass spectrometry - Gross, Jürgen H. (European journal of mass spectrometry, 2020)
In positive-ion direct analysis in real time-mass spectrometry (DART-MS), mono-, di, and trisaccharides form [M+NH4]+ ions. Some of them, in addition, yield abundant [Mn+NH4]+ cluster ions (n = 1-6)), and thus, can serve for mass calibration. Saccharose, C12H22O11, the most common sugar, also termed sucrose, is among the [Mn+NH4]+ cluster ion forming species. Saccharose may therefore be employed as a cheap and ubiquitous mass calibration standard. The extent of saccharose cluster ion formation depends on the temperature of the DART gas, sample load, and instrumental parameters like trapping conditions of ions prior to mass analysis. This study identifies optimized experimental conditions and demonstrates the application of saccharose cluster ion-based mass calibration for accurate mass measurements in DART mode on a Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometer.